2011
DOI: 10.1128/jcm.00273-11
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Parallel Detection of Viral Pathogens in Clinical Samples by Use of a Metagenomic Approach

Abstract: Viral infectious diseases represent a major threat to public health and are among the greatest disease burdens worldwide. Rapid and accurate identification of viral agents is crucial for both outbreak control and estimating regional disease burdens. Recently developed metagenomic methods have proven to be powerful tools for simultaneous pathogen detection. Here, we performed a systematic study of the capability of the short-read-based metagenomic approach in the molecular detection of viral pathogens in nasoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 27 publications
4
125
4
Order By: Relevance
“…In addition, increasing numbers of non-coding RNAs have been identified that play a role in human cancers [34][35][36]. In the current study, we observed that certain non-coding RNAs were able to regulate gene expression.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, increasing numbers of non-coding RNAs have been identified that play a role in human cancers [34][35][36]. In the current study, we observed that certain non-coding RNAs were able to regulate gene expression.…”
Section: Discussionsupporting
confidence: 55%
“…Another NGS diagnostic approach is to use preferential amplification of pathogenic sequences (PATHseq) to identify nonhuman sequences (304). There are now multiple examples of NGS being used to diagnose viral infections in human patients in a nonbiased manner (305)(306)(307). A more routine role of NGS is thought to be possible with computing technology and decreases in cost (308).…”
Section: Whole-genome Sequencing and Next-generation Sequencingmentioning
confidence: 99%
“…A previous metagenomic study on nasopharyngeal aspirate samples from patients with acute lower respiratory tract infections revealed that up to ϳ95% of raw NGS reads were of human DNA (9). The subtraction of human sequences from large NGS data sets can be a lengthy process, requiring significant computational power which may not be available to most clinical laboratories.…”
mentioning
confidence: 99%